Experimental Research Methods“Validity in Experimental Psychology Research” - Fathimah Az Zahra; Rahma Paramitha Lubis; Zahra Wirani (Psikologiya Journal, 2024)
The experimental method is one of the main approaches in psychological research that allows for causal inference. In experiments, researchers examine human behavior from various aspects, such as cognitive, personality, and motivation. The validity of experimental research is a measure of the extent to which the research is precise and reliable in measuring what it is intended to measure. Validity is concerned with the correctness of the inference that results from the research. This article discusses validity in psychology experimental research, including the definition, function, and types of validity. Internal validity indicates the extent to which the cause-and-effect relationship observed in the experiment corresponds to the treatment given, while external validity evaluates the extent to which the results of the study can be generalized to a wider population. Factors such as sample peculiarities and test reactivity affect external validity. Understanding validity in experimental research is important to ensure the accuracy and reliability of the research results as well as their generalizability to different contexts and populations.